2014
DOI: 10.1038/ncomms6090
|View full text |Cite
|
Sign up to set email alerts
|

Determining volcanic eruption styles on Earth and Mars from crystallinity measurements

Abstract: Both Earth and Mars possess different styles of explosive basaltic volcanism. Distinguishing phreatomagmatic eruptions, driven by magma-water interaction, from 'magmatic' explosive eruptions (that is, strombolian and plinian eruptions) is important for determining the presence of near-surface water or ice at the time of volcanism. Here we show that eruption styles can be broadly identified by relative variations in groundmass or bulk crystallinity determined by X-ray diffraction. Terrestrial analogue results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Calibration standards can be easily created by mixing powdered minerals (e.g. olivine, pyroxene, plagioclase) with powdered glass in known proportions to simulate volcanic material of varying crystallinities (e.g., Rowe et al, 2012, Wall et al, 2014.…”
Section: Crystallinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Calibration standards can be easily created by mixing powdered minerals (e.g. olivine, pyroxene, plagioclase) with powdered glass in known proportions to simulate volcanic material of varying crystallinities (e.g., Rowe et al, 2012, Wall et al, 2014.…”
Section: Crystallinitymentioning
confidence: 99%
“…Quantification and characterization of amorphous materials is an important area of research in terrestrial and planetary sciences (e.g., Schmidt et al, 2009, Dehouck et al, 2014, Wall et al, 2014, Morris et al, 2016, Zorn et al, 2018. Powder X-ray diffraction (XRD), although primarily a tool for characterization of crystalline materials, also provides a means to investigate amorphous materials (e.g., Rowe et al, 2012, Achilles et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…We combine X‐ray fluorescence (XRF), X‐ray diffraction (XRD), and thin section analysis to obtain the elemental and mineralogical composition of the pre‐reacted rock samples. The volcanic glass content of the samples is quantified following the methodology described by [ Wall et al , ]. Figure shows X‐ray diffractograms with the amorphous content analysis, as well as thin sections photomicrographs of samples P2F and P3.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Thus, a method is needed for differentiating volcanic deposits produced by these two types of explosive eruptions. Previous studies have shown that the crystallinity of volcanic tephra, as determined by X-ray diffraction (XRD), can be used to infer eruption style [Wall et al, 2014]; however, this technique is only applicable to landed investigations [Blake et al, 2012].…”
Section: Introductionmentioning
confidence: 99%